The Euro area sovereign debt crisis: safe haven, credit rating agencies and the spread of the fever from Greece, Ireland and Portugal - Roberto A. De Santis (European Central Bank (ECB), 2012)
Since the intensification of the crisis in September 2008, all euro area long-term government bond yields relative to the German Bund have been characterised by highly persistent processes with upward trends for countries with weaker fiscal fundamentals. Looking at the daily period 1 September 2008 - 4 August 2011, we find that three factors can explain the recorded developments in sovereign spreads: (i) an aggregate regional risk factor, (ii) the country-specific credit risk and (iii) the spillover effect from Greece. Specifically, higher risk aversion has increased the demand for the Bund and this is behind the pricing of all euro area spreads, including those for Austria, Finland and the Netherlands. Country-specific credit ratings have played a key role in the developments of the spreads for Greece, Ireland, Portugal and Spain. Finally, the rating downgrade in Greece has contributed to developments in spreads of countries with weaker fiscal fundamentals: Ireland, Portugal, Italy, Spain, Belgium and France.
Keywords: G15; F36; 330; credit ratings; Sovereign Spreads; spillovers